Factors affecting parental role adaptation in parents of preterm infants after discharge: a cross-sectional study - Li, Jia; Zhang, Xiaohong; Ye, Fei; Cheng, Xiaolin; Yu, Liping (Frontiers in Psychology, 2024)
Background Parenting a preterm infant can be incredibly challenging and stressful, particularly in the first year after discharge. Desirable parental role adaptation leads to appropriate parenting behaviors and parent-infant interaction, which are essential to child health and development. Aim To investigate the level of parental role adaptation and its influencing factors among parents of preterm infants in the first year after hospital discharge according to Belsky’s parenting process model among parents of preterm infants in the first year after hospital discharge. Methods A cross-sectional study design was adopted using convenience sampling. Data were collected using the Parental Role Adaptation Scale (PRAS) in parents with preterm infants, the Perceived Social Support Scale (PSSS), the Coping Adaptation Processing Scale (CAPS-15), and a sociodemographic questionnaire. Descriptive statistics, non-parametric tests, Spearman correlation analyses, and multivariate linear regression were used to analyze the data. Results In total, 300 Chinese parents were included in the analysis. In the multivariate analysis, first-time parent (p = 0.003), master’s degree and above (p = 0.042), coping adaptation processing (p = 0.000), residence location (towns: p = 0.019, city: p = 0.028), monthly family income (6000–10,000: p = 0.000, >10,000: p = 0.000), and perceived social support (p = 0.001) were all significant predictors of parental role adaptation and collectively accounted for 56.8% of the variation in parental role adaptation of parents with preterm infants (F = 16.473, p < 0.001). Coping adaptation processing mediated the relationship between perceived social support and parental role adaptation (95% bootstrap CI = 0.022, 0.130). Conclusion Chinese parents of preterm infants experience a moderate level of parental role adaptation when their child is discharged from the hospital to home. Parents who are not first-time parents, have master’s degrees or above, live in towns or cities, have higher coping and adaptation abilities, have high monthly family income, and greater perceived social support have a higher level of parental role adaptation. Healthcare providers should pay more attention to parents with low socioeconomic status and encourage them to improve their coping and adaptation abilities and to utilize their formal and informal social support networks.